Beyond Compartmentalized Atlantics: A Case for Embracing the Atlantic from Spanish American Shores - Bassi, Ernesto (History compass, 2014)
Despite the recent surge of Atlantic histories that pursue connections across political boundaries, compartmentalized Atlantics still dominate the field's historiographical map. This paper presents some of the most recent efforts to construct Atlantic histories that cut across political borders and depict the entangled nature of lived experiences in the early modern Atlantic world. In particular, focusing on recent works that look at islands as loci of entanglement and studies that follow individuals as they crossed political borders, this article suggests that historians of Spanish America should embrace the Atlantic as a way to contribute to the production of an Atlantic history that more faithfully represents the lived experiences and collective imaginaries of Atlantic dwellers.